Asymptotic integration of linear differential-algebraic equations - Vu Hoang Linh; Nguyen Tuan (Electronic Journal of Qualitative Theory of Differential Equations, 2014)
This paper is concerned with the asymptotic behavior of solutions of linear differential-algebraic equations with asymptotically constant coefficients. Some results of asymptotic integration which are well known for ordinary differential equations (ODEs) are extended to differential-algebraic equations (DAEs).